2016
DOI: 10.1136/bmj.i2037
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women in war zones

Abstract: Forgotten victims, killed by violence and by a lack of available care

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Our study found that the destruction of health care infrastructure in the occupied areas deprived pregnant women of quality health care for several months. This corresponds to previous research by Akol et al [ 11 ], which suggests that the lack of antenatal and perinatal care in war increases the risk of anemia, malnutrition, and concomitant disease. Our study has not identified malnutrition, but has rather found unbalanced nutrition practices, the negative health effects of which tend to appear later and could thus not be felt or measured at this point of research.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that the destruction of health care infrastructure in the occupied areas deprived pregnant women of quality health care for several months. This corresponds to previous research by Akol et al [ 11 ], which suggests that the lack of antenatal and perinatal care in war increases the risk of anemia, malnutrition, and concomitant disease. Our study has not identified malnutrition, but has rather found unbalanced nutrition practices, the negative health effects of which tend to appear later and could thus not be felt or measured at this point of research.…”
Section: Discussionsupporting
confidence: 91%
“…WHO and UNICEF [ 10 ] have reported severe disruptions of vaccination practices in Ukraine since 2014. Moreover, conflict and displacement also have significant harmful psychological impact on both mothers and children [ 11 ]. However, these issues are often overlooked by traditional humanitarian response measures, which tend to focus on the provision of basic services, such as food and water, shelter, sanitation, and medical emergency services [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…But these nuances might get lost when tabloids and/or persons with different agendas become involved, which has happened before in relation to this method [ 143 ], see also Wikipedia. Women with a completed family who have been offered and have accepted an opportunistic TO might consider themselves exceptionally lucky in future if DMPA is unobtainable because of physicians’ and nurses’ strikes, because USAID lost funding or because of civil war with perhaps many cases of rape [ 163 , 164 ].…”
Section: Hiv/aidsmentioning
confidence: 99%
“…These vulnerabilities increase in conflict situations, and as a result, structural inequalities rooted in gender norms impact women’s health [ 13 ]. For instance, studies have identified that during conflicts, girls and women experience poor access to essential sexual and reproductive health services [ 17 ], high rates of unsafe abortions [ 13 , 14 ], and increases in maternal mortality [ 12 ]. In summary, the evidence strongly suggests girls and women in conflict settings are more likely to face social inequalities accessing sexual, reproductive and maternal health care, and these inequalities may worsen or broaden over time.…”
Section: Introductionmentioning
confidence: 99%